FAKTOR-FAKTOR YANG MEMENGARUHI STRUKTUR MODAL - PUTIHTA, WULAN SUCI RAMADHIA; ARILYN, ERIKA JIMENA (E-Jurnal Manajemen Trisakti School of Management (TSM), 2024)
The purpose of this research is to acknowledge the factors that influence the company’s capital structure of companies in Indonesia. This research conducted to empirically test and analyze the relationship regarding the influence of independent variables included profitability, tangibility, sales growth, business risk and liquidity toward dependent variable capital structure. The research about capital structure is re-examinated due to inconsistencies in the result of the previous research. The object of this research is company in subsector Food and Beverage that listed in Indonesia Stock Exchange period 2013-2022. The sample of this research consist of 19 companies with 190 data selected by purposive sampling method, the data is processed and tested using panel data regression in Eviews 12 with random effect model for the hypothesis testing. The result of this research shows that profitability, sales growth and liquidity influence capital structure, while tangibility and business risk do not influence capital structure.